The Implementation of Artificial Intelligence on Accounting In Indonesia: A Literature Study - Khairul Saleh L. Tobing; Muhammad Nur; Dhieka Avrilia Lantana; Kumba Digdowiseiso; Shayuti Mohd Adnan (CV ODIS, 2023)
The rapid growth of Artificial Intelligence (AI) is transforming accounting practices in Indonesia. This study uses a qualitative literature review approach to investigate AI implementation in Indonesian accounting. It focuses on identifying implementation challenges, and goals, and summarizes previous research findings. AI adoption delivers substantial benefits, enhancing accuracy, efficiency, and transparency across various areas, such as Sharia-compliant accounting, employee training, financial data analysis, and conservative accounting principles. Despite these advantages, challenges loom. These include a lack of AI awareness and technical skills among accountants, data security concerns, integrating AI with existing systems, ethical considerations, and ensuring data quality. Overcoming these challenges demands dedicated efforts from accountants, businesses, and relevant institutions to unlock the full potential of AI in Indonesian accounting practices